Hubungan antara tekanan psikologikal dan kemarahan dengan tingkah laku buli dalam kalangan pelajar universiti - Mohd Suhaimi Mohamad; Nazirah Hassan; Nasrudin Subhi; Muzamir Wan Nazri (Penerbit Universiti Kebangsaan Malaysia, 2021)
Bullying behavior among students is increasingly growing in the higher education institutions. This study was conducted to identify psychological stress, anger and bullying behavior among students in the Faculty of Social Science and Humanities UKM. This was a quantitative study using the survey method through a set of questionnaires to 100 FSSK students from various courses of study. The questionnaire consisted of three instruments: Peer Relations Questionnaire (PRQ), State-Trait Anger Expression Inventory-2 (STAXI-2) and General Health Questionnaire (GHQ-12). The results show that bullying behavior among FSSK UKM students was moderate meanwhile the level of anger and psychological stress level of the students was low. The level of psychological stress of students has significant relationship with the level of anger and bullying behavior among FSSK UKM students. Therefore, the university should ensure that bullying behavior does not happen in campus and need to do screening on the anger and psychological stress of the students as a whole to avoid mental health issues to happen. All parties need to play a role to prevent bullying and to reduce the aggressive attitude and mental problems among university students.